Determinants of Youth Unemployment in Pakistan - Imtiaz, Shoaib; Ali, Arshad; Khan, Zeeshan; Ullah, Mohib; Khan, Muhammad; Jacquemod, Julija (International Journal of Economics and Financial Issues, 2020)
Unemployment, particularly youth unemployment, is a big issue that countries are facing globally. It has been a major concern for many countries like Pakistan. In this research, we develop an empirical study on investigating the determinants affecting youth unemployment in Pakistan. This study observes the youth unemployment and the variety of determinants that were identified as political instability, lack of investment, backwardness of agriculture sector, and overpopulation. This study discussed that young people aged (15-24) have been largely affected by the existing recession. This is for the reason that the present youth group is quite big, the longer-term viewpoint for youth unemployment is relatively great and there is a sturdy case for policymakers currently to tackle these problems that the present group is having in finding access to work. It also discusses the need for sufficient employment environment, policy examining, and assessment of the reasons to assist in providing more advanced jobs for youth. The results show that political instability, lack of investment, backwardness of agriculture sector, and overpopulation significantly affect youth unemployment. Keywords: Political instability, lack of investment, backwardness of agriculture sector, overpopulation, youth unemployment, Pakistan JEL Classifications: E24, J43 DOI: https://doi.org/10.32479/ijefi.10386